Metabolomic fingerprinting as a tool for authentication of grapevine (Vitis vinifera L.) biomass used in food production. (1st November 2021) - Stranska, Milena; Uttl, Leos; Bechynska, Kamila; Hurkova, Kamila; Behner, Adam; Hajslova, Jana
Graphical abstract: Highlights: U-HPLC–HRMS/MS fingerprinting reflects changes in the V. vinifera metabolome. Successive extraction with methanol followed by water assures sufficient metabolites yields. PLS/OPLS-DA models so created enabled authentication of V. vinifera leaves and canes. This approach supports the exploitation of V. vinifera by-products for further use. Abstract: Use of 'green biomass' of the grapevine is gradually extending into the food industry. The aim of our study was to demonstrate the potential of metabolomic fingerprinting for characterization of grapevine leaves and canes. Our method comprises successive aqueous-methanolic extractions, followed by U-HPLC–HRMS/MS. For data processing, PCA and (O)PLS-DA methods were utilized, and mathematical models were validated. We showed that from all factors investigated, harvesting season explained most of the variability between samples, followed by locality combined with farming system. The identified statistically significant metabolites for harvesting season models mostly represented the groups of fatty acids, fatty phenols, (lyso)phospholipids, flavonoids and organic acids. For models of localities with different farming systems, majority of identified metabolites significant for organic farming belonged to groups of fatty acids and their derivatives, terpenoids, sterols, and fat soluble vitamins, whereas for conventional farming, the only identified significant metabolites were the pesticide residues.